PENERAPAN MEDIA PEMBELAJARAN KOMIK DIGITAL UNTUK MENGATASI KESULITAN BELAJAR SISWA KELAS 2B MINU KEDUNGREJO PADA MATA PELAJARAN PKN MATERI ATURAN DIRUMAH DAN DI SEKOLAH - Ananda Chumairoh; Aulia Mufidatus Safiani; Putri Yasmin Fazia Risfi; Nur ‘Aisyatir Rodliyah; Muchammad Bachrul Alam; Asnal Mala (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
In today's digital era, teachers are expected to be more competent in delivering learning materials to create an interactive and enjoyable learning environment. Therefore, the use of learning media is crucial, not merely as a supplement, but as an effective tool to help students understand the material more easily. Media plays a significant role in the learning process. However, the teacher's role is also crucial in ensuring that the media used is not boring and can motivate students to learn. This research focuses on the development of learning media in the form of digital comics presented in video format, specifically covering the rules and benefits. Furthermore, this study aims to determine students' responses to the created digital comics. The research used research and development (RD) methods. The media development process followed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. This study involved one teacher and 21 students who actively participated in the learning process. In addition, one material expert and one media expert participated in this study. Data were collected through observations, questionnaires, interviews, and tests. The results showed that the video-based digital comic media was rated "Very Appropriate" by the media expert with a score of 94%. The assessment from the material experts was also nearly identical, at 93%, which falls into the "Very Appropriate" category. Students and teachers gave high practicality ratings, at 88% and 89%, respectively. After using digital comics, students' post-test scores increased to 86%, remaining in the "Very Appropriate" category. The purpose of this study was to determine the impact of ICT-based digital comics on student learning outcomes in Civics (PPKn) in second-grade students at MINU Kedungrejo. Researchers compared two groups, one using digital comics and the other using traditional methods. The results showed that students learning with digital comics experienced improved learning outcomes. This medium is not only engaging but also facilitates understanding and increases student enthusiasm for learning. ICT-based digital comics can be an effective solution for Civics (PPKn) learning in elementary schools.